Levels of (1→3)-β-D-glucan, Candida mannan and Candida DNA in serum samples of pediatric cancer patients colonized with Candida species - Khan Zia U; Burhamah Mona HA; Mokaddas Eiman; Ahmad Suhail (BMC Infectious Diseases, 2010)
Abstract Background Surveillance cultures may be helpful in identifying patients at increased risk of developing invasive candidiasis. However, only scant information exists on the effect of Candida colonization on serum levels of diagnostic biomarkers. This prospective surveillance study determined the extent of Candida colonization among pediatric cancer patients and its possible impact on serum levels of (1-3)-β-D-glucan (BDG), Candida mannan and Candida DNA. Methods A total of 1075 swabs originating from oropharynx (n = 294), nostrils (n = 600), rectum (n = 28), groin (n = 50), ear (n = 54), and axilla (n = 49) of 63 pediatric cancer patients were cultured for the isolation of Candida spp. Patients yielding Candida spp. from any sites were considered as colonized. Serum samples were collected from patients at the time of first surveillance culture for detection of BDG by Fungitell kit and Candida mannan by Platelia Candida Ag. Candida DNA was detected by using panfungal primers and identification was carried out by using species-specific primers and DNA sequencing. Results Seventy-five (7.6%) swab cultures from 35 (55.5%) patients yielded Candida spp. These isolates included C. albicans (n = 62), C. dubliniensis (n = 8), C. glabrata and C. tropicalis (n = 2 each) and C. krusei (n = 1). Eleven patients were colonized at three or more sites. Eight of 36 serum samples from 6 colonized patients yielded BDG values higher than the currently recommended cut-off value of ≥80 pg/ml. However, none of the serum samples yielded Candida mannan levels ≥0.5 ng/ml and PCR test for Candida DNA was also negative in all the serum samples of colonized patients. During the study period, only two colonized patients subsequently developed candidemia due to C. tropicalis. Besides positive blood cultures, C. tropicalis DNA, BDG and Candida mannan were also detected in serum samples of both the patients. Conclusions The present study demonstrates that while mucosal colonization with Candida species in pediatric cancer patients is common, it does not give rise to diagnostically significant levels of Candida mannan or Candida DNA in serum specimens. However, BDG values may be higher than the cut-off value in some pediatric patients without clinical evidence of invasive Candida infection. The study suggests the utility of Candida mannan or Candida DNA in the diagnosis of invasive candidiasis, however, the BDG levels in pediatric cancer subjects should be interpreted with caution.